HUBUNGAN PENGETAHUAN DAN SIKAP MAHASISWI DENGAN SADARI DI POLITEKNIK KESEHATAN DEPARTEMEN KESEHATAN BANJARMASIN JURUSAN KEBIDANAN - Nurlaila, Nurlaila (Politeknik Kementerian Kesehatan Banjarmasin, 2022)
ABSTRACT : Breast cancer is a dreaded breast disorder. In the world it is estimated that 1.2 million women are diagnosed with breast cancer. 500,000 of them died. In Indonesia breast cancer is in second position of cancer types suffered by women and affects 1 in 14 women. The incident of breast cancer is about 100 per 100,000 people per year, more than 50% are found in an advanced stage. In South Kalimantan an average of 70-90% of patients come to the hospital in an advanced stage. Of the 15 midwives, 1 had a breast tumor and 1 had breast cancer. And of the 15 midwives, 3 of them were students of the DIII midwifery program at Health Polytechnic of Health Department Banjarmasin. Of the 3 students, 1 student did not do COB, in fact breast cancer can be prevented with COB. The research aimed to find out the relation of knowledge and attitude of students with COB at Health Polytechnic of Health Department Banjarmasin, Midwifery Major. The results of research showed that 27 people (67.5%) rarely did COB, 20 (50%) students had sufficient level of knowledge and 13 (32.5%) students had a very good attitude towards COB. The results of the chi square test obtained p = 0.556 (p>0.05) with a significance of 5%, meant that there was no relation between knowledge and COB. Furthermore, the value of p=1,000 (p>0.05) obtained, meant that there was no relation between attitude with COB. Keywords: knowledge, attitude, COB